Sistem Informasi Management Warehouse PT. Kreatif Mantani - Fyona Apryanti; Fajar Mutaqin; Khoiriyah; Thoyyibah. T (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
PT. Kreatif Mantani is a construction service company in the field of Mechanical, Electrical and Plumbing which was founded in 2002. Over time, the Company developed in the Trading sector. Installation of IP (Trend Honeywell) based Building Automatic System (BAS) equipment and equipment. CCTV (Samsung & Focus), and has collaborated with leading electronics manufacturers from South Korea in the CCTV field. PT Kreatif Mantani is a company that continues to grow because it has a clear vision and a good work culture. The research conducted by the author is aimed at making a warehousing inventory application at PT. Kreatif Mantani. This application is made using the Waterfall method with a series of processes in the design. The system uses the PHP programming language and MySql database is used as a framework for making the system. The result of the goods inventory information system is that the system can manage goods data, distribute incoming and outgoing goods systematically, making it easier for system users or users to process report printing, export reports and produce appropriate information for the company.